A MULTIDISCIPLINARY APPROACH TO ADJUNCTIVE TREATMENT OF COMORBID UROLOGICAL PATHOLOGY IN PROSTATE CANCER (World Bulletin of Public Health, 2024)
This article explores the importance of using a multidisciplinary approach to the management of concomitant urological pathology in patients with prostate cancer. It discusses the relationship between prostate cancer and urological conditions, provides a literature review, suggests effective methods of integrated care, and provides insight into potential outcomes and debates. Ultimately, it highlights the importance of collaboration between healthcare professionals to optimise patient outcomes.
Keywords: prostate cancer; urological pathology; multidisciplinary approach